Skills and Jobs : Lessons Learned and Options for Collaboration - Sanchez Puerta, Maria Laura; Robalino, David A.; Strokova, Victoria; Lord, Nick; Perinet, Mathilde (World Bank, Washington, DC, 2015)
The accumulation of human capital through the acquisition of knowledge and skills is recognized as central for economic development. More-educated workers not only have better employment opportunities, they earn more and have more stable and rewarding jobs. They are also more adaptable and mobile. Workers who acquire more skills make other workers and capital more productive and, within the firm, they facilitate the adaptation, adoption, and ultimately invention of new technologies. This is crucial for economic diversification, productivity growth, and ultimately raising the living standards of living of the population. The structure of the note is as follows. First, it examines the different types of market failures, and subsequently reviews the role that governments have played in training systems around the world. Finally it offers a set of proposals for reforming and improving these systems to improve labor market outcomes.